Dinamika Pengalaman Tinnitus Subjektif Pada Mahasiswa Kedokteran Dalam Tekanan Akadmeik Dengan Pendekatan Fenomenologis - Ebenson Purba; Agnes Juni Jelitas Sitohang; Emaston Tito Julianda Sinaga (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Medical students represent a population highly vulnerable to intense academic pressure which can clinically trigger or exacerbate sensory perception disorders such as subjective tinnitus. This study explores the lived experience dynamics of medical students dealing with subjective tinnitus amidst academic pressure through a descriptive phenomenological approach. Data collection was carried out through in-depth interviews with eight medical students as participants selected via purposive sampling. Thematic analysis techniques were used to process the data, successfully identifying four primary dynamics. These dynamics include tinnitus as a cognitive distraction in study concentration, an increase in tinnitus intensity during block exam periods, the emergence of somatic impacts such as chronic sleep disturbances, and self-coping efforts through sound distraction with declining effectiveness during peak stress levels. These results emphasize that tinnitus in medical students serves as a physical indicator of psychological distress. Educational institutions should provide integrated mental health support systems to help students manage the impacts of tinnitus and academic pressure more comprehensively.